MiRNA Expression in Psoriatic Skin: Reciprocal Regulation of hsa-miR-99a and IGF-1R - Lerman, Galya (Public Library of Science, 2011)
BACKGROUND: Psoriasis is a complex disease at the cellular, genomic and genetic levels. The role of microRNAs in skin development was shown in a keratinocyte-specific Dicer knockout mouse model. Considering that two main characteristics of psoriasis are keratinocytes hyperproliferation and abnormal skin differentiation, we hypothesized that aberrant microRNA expression contributes to the psoriatic phenotype. Here, we describe the differential expression of miRNAs in psoriatic involved and uninvolved skin as compared to normal skin, revealing an additional aspect of this complex disorder. METHODOLOGY/PRINCIPAL FINDINGS: Expression arrays were used to compare microRNA expression in normal skin versus psoriatic involved and uninvolved skin. Fourteen differentially expressed microRNAs were identified, including hsa-miR-99a, hsa-miR-150, hsa-miR-423 and hsa-miR-197. The expression of these microRNAs was reevaluated by qPCR. IGF-1R, which is involved in skin development and the pathogenesis of psoriasis, is a predicted target of hsa-miR-99a. In an in situ hybridization assay, we found that IGF-1R and miR-99a are reciprocally expressed in the epidermis. Using a reporter assay, we found that IGF-1R is targeted by hsa-miR-99a. Moreover, over expression of miR-99a in primary keratinocytes down-regulates the expression of the endogenous IGF-1R protein. Over expression of miR-99a also inhibits keratinocyte proliferation and increases Keratin 10 expression. These findings suggest that overexpression of hsa-miR-99a in keratinocytes drives them towards differentiation. In primary keratinocytes grown in high Ca(++), miR-99a expression increases over time. Finally, we found that IGF1 increases the expression of miR-99a. CONCLUSIONS/SIGNIFICANCE: We identified several microRNAs that are expressed differentially in normal and psoriatic skin. One of these miRNAs is miR-99a that regulates the expression of IGF-1R. Moreover, miR-99a seems to play a role in the differentiation of keratinocytes. We suggest that miR-99a is one of the regulators of the IGF-1R signaling pathway in keratinocytes. Activation of IGF1 signaling results in elevation of miR-99a which represses the expression of IGF-1R.